Ce3+ doped glass for radiation detection material. (November 2018) - Wantana, N.; Kaewnuam, E.; Chanthima, N.; Kaewjaeng, S.; Kim, H.J.; Kaewkhao, J.
Abstract: The Ce 3+ doped sodium-gadolinium-aluminum-phosphate glasses, with 20Na2 O− 10Gd2 O3 − 10Al2 O3 − (60-x)P2 O5 − xCeF3 (where x = 0.00, 0.10, 0.50, 1.50, 2.00 and 3.00 mol%) composition, have been measured and analyzed. The prepared glasses were studied various properties such as physical, optical, luminescence and scintillation. The densities of glasses were found to increase with the concentration of CeF3 while molar volumes decreased. The value of absorption edge is shifted from 313 nm of host glass to longer wavelength with CeF3 doping. The indirect and direct band gap decreased with increasing CeF3 content which corresponded to the molar volume reduction representing the enhancement of non-bridging oxygen (NBO) number in glass network. Photoluminescence spectra showed the strong emission bands centered between 325 and 347 nm under Ce 3+ directly excitation and Gd 3+ excitation. The optimum concentrations of CeF3 concentration in this glass is 2.00 mol% as it resulted the maximum emission intensity. The strongest emission band of x-ray induced optical luminescence is around 375 nm. The integrated scintillation efficiency of 2.0 mol% CeF3 doped glass was 9.6% compared with bismuth germanium oxide (BGO) crystal. The most dominant decay times of 2.0 mol% doped glass was fast as 26.8 ns that performed the rapid response with coming excitation energy. In this work, our developed glasses performed the strong and fast luminescence signal which can be applied as the scintillation material in radiation detector.